Peran Kepuasan Kerja dan Keterikatan Kerja Terhadap Disiplin Kerja Karyawan di PT. X - Sunyoto, Rivaldi Suryonugroho; Wulanyani, Ni Made Swasti (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the key factors contributing to the seamless operation of business processes within a company is the elevated level of discipline exhibited by each employee. With such discipline, the company's performance is likely to improve. Work satisfaction and engagement closely influence the degree of work discipline. This study aims to determine the role of work satisfaction and work engagement on employee work discipline within PT. X. The measuring tools used are Work Satisfaction, Work Engagement, and Work Discipline Scales. The study encompasses a sample of 290 PT. X employees. The sampling technique used in this study is simple random sampling using multiple regression data analysis techniques. The results of the multiple regression analysis tests showed a value of 0.717, which means work satisfaction and work engagement has a role in work discipline by 71.7%. The value of the unstandardized beta coefficient on work satisfaction is 0.333 with a significance of 0.000 (p < 0.05), which means that work satisfaction has a role in work discipline. The value of the unstandardized beta coefficient on work engagement is 0.569 with a significance of 0.000 (p < 0.05), which means that work engagement has a role in work discipline. The outcomes of this study provide valuable insights for employees and companies alike, emphasizing the critical importance of maintaining work satisfaction and engagement to enhance employee work discipline.